Increase in stress on infrastructure facilities due to natural disasters. Issue 1 (27th May 2016) - Choi, Juyeong; Deshmukh, Abhijeet; Hastak, Makarand
ABSTRACT: The services of infrastructure are often compromised in a post-disaster situation. This could be due to a direct physical impact on the infrastructure or due to a cascading impact resulting from reduced services of the supporting infrastructure. The reduced infrastructure services are unable to adequately meet the post-disaster community needs. Therefore, infrastructure facilities are likely to be operated with high stress on their capacities above the allowable stress (i.e. designed capacities) for meeting the services required. The system is unable to sustain the required serviceability level without the infusion of additional capacities when the stress level exceeds the limit stress. For example, after Haiti's devastating earthquake, disrupted utility services, limited road networks, and the lack of civic governance influenced the capacity of all essential service providers. Furthermore, the earthquake-impacted hospitals had limited resources such as patient beds, medical staff, medical supplies and equipment for meeting the increased health needs of the community. As a result, the hospital experienced increased levels of stress related to services as they were unable to adequately meet the community health needs without external assistance from NGOs or other entities. Therefore, understanding the stress level in post-disaster infrastructure is critical for community recovery. This paper presents a new framework to (i) explore and investigate varying functional stress level in infrastructure under various disaster scenarios and (ii) develop strategies for alleviating increased stress levels in order to facilitate the recovery process. The research framework is explained using a hypothetical situation focusing on the operation of power facilities in a post-disaster situation. The proposed unique approach enables the development of sustainable mitigation strategies by relieving the stress level in critical infrastructure while ensuring to meet recovery demands at an acceptable level.